Beyond continuity : script supervision for the modern filmmaker - Cybulski, Mary (Focal Press, 2014)
"A guide to the craft of script supervising, Beyond Continuity features practical instruction through real-world examples demonstrating and explaining the skills needed by a professional script supervisor. Mary Cybulski, one of Hollywood's premier script supervisors, imparts her sage wisdom as she walks you through the process of training and working as a professional script supervisor, covering the basic skills of breaking down a script, taking notes on set, matching, cheating, determining screen direction, and knowing what the director, actors, and editor expect from a script supervisor. She also details many of the more subtle, but just as important skills-- how to get a job, how to think like an editor, how to tell what is important in a script and on set, how to get along with the cast and crew, and how not to get overwhelmed when there is too much information to process"--